Layered exfoliable crystalline materials based on Sm-, Eu- and Eu/Gd-2-phenylsuccinate frameworks. Crystal structure, topology and luminescence properties - Gomez, Germán Ernesto (2015)
Three new layered metal–organic frameworks (MOFs) based on 2-phenylsuccinic acid (H2psa) and lanthanide ions with the formula [Ln2(C10H8O4)3(H2O)] (Ln = Eu, Sm and Eu–Gd) have been synthesized under solvothermal conditions and fully characterized by single-crystal X-ray diffraction, thermal and vibrational analyses. The compounds are isostructural featuring 2D frameworks that consist of infinite zigzag chains composed of [LnO8] and [LnO8(H2O)] edge-sharing polyhedra linked by psa ligands leading to layers further connected by weak π–π interactions in an edge orientation. Moreover, a topological study was carried out to obtain the simplified net for better comparison with structurally related compounds. The Eu-psa crystals were exfoliated into nanolayers after miniaturization by addition of sodium acetate as a capping agent in the reaction medium. Scanning electron microscopy was applied to characterize the miniaturized samples whereas the exfoliated hybrid nanosheets were studied by atomic force microscopy. The photoluminescence (PL) properties of the bulk compounds as well as the miniaturized and exfoliated materials were investigated and compared with other related ones. An exhaustive study of the Eu(III)-based MOFs was performed on the basis of the obtained PL parameters (excitation and emission spectra, kr, knr, intrinsic quantum yields and lifetimes) to explore the underlying structure–property relationships.